The institutionalization of Jesus" charismatic authority, Part 1: Indirect Christology - direct Christology 1 - Dreyer, Yolanda (Hervormde teologiese studies, 2000)
This study concerns an investigation of the evolution of the Jesus tradition. Christological titles are studied in terms of the social theory of the institutionalization of charismatic authority. It makes use of Anthony Thiselton's and Bengt Holmberg's application of Max Weber's social theory. It is argued that the followers of Jesus acknowledged and expressed his authority by means of naming. These "names" developed into "titles" when the post-Easter followers of Jesus allocated power to him. The process of the institutionalization of Jesus' charismatic authority relates to the transmission from the oral tradition of Jesus' sayings and deeds to the written evidence. The article emphasizes the work done by the Jesus Seminar. The following "rules of written evidence" are considered: clustering and contexting; revision and commentary; false attribution; difficult sayings and the process of christianising. In Part 2 of the study, Weber,s social theory is applied to the Christological title "Son of Man".